Blood Group Antigens Visualisation on Leukocytes - Kravchun, Pavlo Grigorovich; Leontyeva, Frida Solomonivna; Povelichenko, Olena Dmytrivna; Dielievska, Valentyna Yuriivna (Scripta Medica, 2024)
Background/Aim: The leukocytes have been reported to contain blood group specific antigens, that are clinically relevant, however visualisation of A and B group antigens on leukocytes is a big issue. In cases of ABO discrepancies weak blood group antigens on nuclear cells have been demonstrated by using expensive techniques. Thus, the development of the method of the detection of weak blood group antigens on leukocytes available for any laboratory technician is hardly essential. The study aimed to reveal and analyse A and B blood group specific adsorbing antigens on leukocytes and erythrocytes and to develop a method for visualisation of weak blood group antigens on leukocytes. Methods: Polyclonal and monoclonal anti-A and anti-B antibodies, received from international laboratories according to the program of Workshop IV, held in Paris, 2000, were used for the study. Mixed agglutination reaction was performed as the method for visualisation of weak blood group antigens on leukocytes as nuclear cells. Results: Polyclonal sera from O blood group persons without weak blood group antigens in contrast to monoclonal antibodies demonstrated the ability to reveal weak blood group specific antigens on leukocytes by the method of mixed agglutination reaction. However, the test erythrocytes from the persons with increased levels of platelets and erythrocyte sedimentation rate did not allow to visualise weak antigen expression on the studied leukocytes in contrast to the persons with normal levels of platelets and erythrocyte sedimentation rate, that successfully formed mixed agglutinates with weak blood group antigens on leukocytes in mixed agglutination reaction. The leukocytes suspended in 0.9 % saline (as a diluent) incubated with the mixture of the serum with 0.9 % saline (1:2) led to the formation of specific agglutinates with test erythrocytes. The experiments with different temperature regimes and time of incubation demonstrated the usefulness of the studied method in specific leukocytes antigen visualisation during prolonged incubation at 4 °C. The persons with weak group A and B antigens, revealed on the leukocytes by the studied method, demonstrated decreased level of erythrocytes, platelets, titre of corresponding warm agglutinating antibodies (less than 1:8) and increased erythrocyte sedimentation rate. Conclusion: The mixed agglutination reaction with prolonged incubation at 4 °C and the use of the selected polyclonal sera and test erythrocytes from the donors with normal values of platelets and erythrocyte sedimentation rate may be used for weak blood group antigens detection on leukocytes. The donors of the sera and test erythrocytes used in mixed agglutination reaction should be investigated on common blood analysis, agglutinating titre of corresponding warm group specific antibodies and presence of weak blood group antigens.